A composite oxygen-reduction electrode composed of SrSc 0.2Co0.8O3-d perovskite and Sm 0.2Ce0.8O1.9 for an intermediate-temperature solid-oxide fuel cell - An, B.; Zhou, W.; Guo, Y.; Ran, R.; Shao, Zongping (Elsevier Ltd, 2010)
SSC (70 wt.% SrSc0.2Co0.8O3-d)-SDC (30 wt.% Sm0.2Ce0.8O1.9) composite was evaluated as cathode for intermediate-temperature solid-oxide fuel cells. The effect of firing temperature on the chemical interaction between SSC and SDC was characterized by oxygen-temperature programmed desorption (O2-TPD) techniques. Certain type of phase reactions occurred between SSC and SDC at calcination temperatures higher than 950 °C. The conductivity of the composite was measured by a four-prober direct current technique. The electro-catalytic activity of the composite electrode for oxygen reduction was measured by electrochemical impedance spectroscopy (EIS) in a symmetric cell configuration. The electrode fired at 950 °C showed the best performance. By applying the SSC + SDC-composite electrode, a cell with a ~20-µm thick SDC electrolyte delivered a peak power density of 760 mW cm-2 at 600 °C. This suggested that an SSC + SDC-composite electrode may be a promising cathode for intermediate-temperature solid-oxide fuel cells. © 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.